Small Interference RNA Targeting Connexin-43 Improves Motor Function and Limits Astrogliosis After Juvenile Traumatic Brain Injury. (June 2019) - Ichkova, Aleksandra; Fukuda, Andrew M.; Nishiyama, Nina; Paris, Germaine; Obenaus, Andre; Badaut, Jerome
Juvenile traumatic brain injury (jTBI) is the leading cause of death and disability for children and adolescents worldwide, but there are no pharmacological treatments available. Aquaporin 4 (AQP4), an astrocytic perivascular protein, is increased after jTBI, and inhibition of its expression with small interference RNA mitigates edema formation and reduces the number of reactive astrocytes after jTBI. Due to the physical proximity of AQP4 and gap junctions, coregulation of AQP4 and connexin 43 (Cx43) expressions, and the possibility of water diffusion via gap junctions, we decided to address the potential role of astrocytic gap junctions in jTBI pathophysiology. We evaluated the role of Cx43 in the spread of the secondary injuries via the astrocyte network, such as edema formation associated with blood–brain barrier dysfunctions, astrogliosis, and behavioral outcome. We observed that Cx43 was altered after jTBI with increased expression in the perilesional cortex and in the hippocampus at several days post injury. In a second set of experiments, cortical injection of small interference RNA against Cx43 decreased Cx43 protein expression, improved motor function recovery, and decreased astrogliosis but did not result in differences in edema formation as measured via T2-weighted imaging or diffusion-weighted imaging at 1 day or 3 days. Based on our findings, we can speculate that while decreasing Cx43 has beneficial roles, it likely does not contribute to the spread of edema early after jTBI.